Hospital and economic burden of influenza-like illness and lower respiratory tract infection in adults ≥50 years-old - Cecilia Trucchi; Chiara Paganino; Andrea Orsi; Daniela Amicizia; Valentino Tisa; Maria Francesca Piazza; Domenico Gallo; Simona Simonetti; Bruno Buonopane; Giancarlo Icardi; Filippo Ansaldi (BMC Health Services Research, 2019)
Abstract Background Influenza-like illnesses (ILIs) and lower respiratory tract infections (LRTIs) cause substantial morbidity and mortality worldwide. The study assessed the health and economic burden of ILI and LRTI according to age and comorbidities, since available evidence is limited and heterogeneous. Method The prevalence of comorbidities, the seasonal incidence rates and the mean and per capita direct costs of ED accesses for ILI/LRTI, whether followed by hospitalization or not, recorded in adults aged ≥50 years over the last 6 years, in the referral hospitals located in the Genoese metropolitan area (Liguria, Italy) where the syndromic surveillance system is active, were evaluated through a retrospective observational study. Comorbidities were estimated through the Chronic Condition Data Warehouse that integrates multiple Medicare data sources. A comparison with the administrative healthcare International Classification of Diseases-9th revision-Clinical Modification (ICD-9-CM)-based data was also conducted. Results The prevalence of subjects with ≥1 comorbidity ranged from 23.49 to 59.92%. The most prevalent all-age comorbidities were cardiovascular diseases and cancer. The overall ILI/LRTI incidence rate was 6.73/1000 person-years, almost double the value derived from routine data, and increased with age. The highest rates were observed in patients with renal failure and bronchopneumopathies. The mean cost of ED accesses/hospitalization for ILI/LRTI was €3353 and was almost twice as high in the ≥85 years as in the youngest age-group. The highest mean costs were observed in patients with renal failure and cancer. The per capita costs increased from €4 to €71 with age, and were highest in patients with renal failure and bronchopneumopathy. Conclusion The burden of ILIs/LRTIs in terms of ED accesses and hospitalizations in adults aged ≥50 years is heavy, and is related to increasing age and, especially, to specific comorbidities. These results could contribute to revising age- and risk-based anti-influenza and -pneumococcus immunization strategies.